عدم الاختصاص والنتائج المترتبة عليه - دراسة تحليلية تطبيقية في الدعوى المدنية - حسين, سەركەوت اسماعيل (Journal of Legal and Political Studies, 2013)
The rules of jurisdiction in each country working to identify Maidkhal within this jurisdiction of the courts of that State has Hdvambeshra is to determine whether the courts competent or not to consider the dispute raised before them, and raises the theory of the jurisdiction of the courts of many legal problems and the main problems is the problem of violation rules of jurisdiction which have a legal condition called status (lack of jurisdiction). May raise the rules of jurisdiction significant problems in the practical application, prosecutor may raise his claim to the competent court, is that the court may decide the case or refuse to be considered? Maidq often controls established by the legislature to determine the jurisdiction of each of the judicial bodies and sometimes up to mystery, Maehmna in Atarhzh study Hothdid violation of the rules of jurisdiction in a civil action, and determine the extent and consequences.
Keywords: Rule of Jurisdiction; competent court; judicial bodies; Violation of rules